The need for environmental surveillance to understand the ecology, epidemiology and impact of Cryptococcus infection in Africa - Edwards,HM; Cogliati,M; Kwenda,G; Fisher,MC (FEMS Microbiology Ecology, 2021)
ABSTRACT Our understanding of the pathogenic yeasts Cryptococcus neoformans and Cryptococcus gattii has been greatly enhanced by use of genome sequencing technologies. Found ubiquitously as saprotrophs in the environment, inhalation of infectious spores from these pathogens can lead to the disease cryptococcosis. Individuals with compromised immune systems are at particular risk, most notably those living with HIV/AIDS. Genome sequencing in combination with laboratory and clinical studies has revealed diverse lineages with important differences in their observed frequency, virulence and clinical outcomes. However, to date, genomic analyses have focused primarily on clinical isolates that represent only a subset of the diversity in the environment. Enhanced genomic surveillance of these yeasts in their native environments is needed in order to understand their ecology, biology and evolution and how these influence the epidemiology and pathophysiology of clinical disease. This is particularly relevant on the African continent from where global cryptococcal diversity may have originated, yet where environmental sampling and sequencing has been sparse despite harbouring the largest population at risk from cryptococcosis. Here, we review what scientifically and clinically relevant insights have been provided by analysis of environmental Cryptococcus isolates to date and argue that with further sampling, particularly in Africa, many more important discoveries await.